The anarchist cookbook : DevOps and Agile recipes for blowing up the waterfall (O'Reilly Media, 2016)
"LeaseWeb has started a transition toward a more Agile and empowered engineering culture. Arnoud Vermeer offers a summary of things LeaseWeb did to foster the change, the impact they had, and lessons learned along the way. This clip comes from the 2016 Velocity conference in Amsterdam."--Resource description page